HUBUNGAN MOTIVASI BELAJAR DAN KEPERCAYAAN DIRI DENGAN HASIL BELAJAR SISWA KELAS V SDN SE-KECAMATAN BULUSPESANTREN TAHUN AJARAN 2018/2019 - Isnaeniatun Umifaiqoh; Joharman Joharman; Ngatman Ngatman (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2020)
Abstract:This study aimed to prove the existence of (1) positive correlation of motivation to learn with mathematics learning achievement; (2) positive correlation of self-confidence with mathematics learning achievement; (3) positive correlation of  motivation to learn and self-confidence with mathematics learning outcomes of grade V students of public elementary schools in Buluspesantren Subdistrict in Academic Year 2018/2019. This research is a quantitative study with a correlational method. Sampling was done by cluster random sampling technique. In the analysis of research data, the researcher used SPSS version 21 application in analyzing data correlation. The results showed that the correlation between learning motivation and self-confidence with mathematics learning outcomes was 0.7 and the contribution was 49.1%. Based on the analysis and discussion of the results of the study, it can be concluded that there is a relationship between motivation to learn and self-confidence with the results of mathematics learning in the fifth grade students of public elementary schools in Buluspesantren Subdistrict.